Beyond the motivation theory of destination image - Madden, Ketwadee; Rashid, Basri; Zainol, Noor Azimin (Fakultet za menadžment u turizmu i ugostiteljstvu u Opatiji, 2016)
Purpose – The existing literature has accepted the view that the destination image can be explained by the motivation theory.According to this theory the destination image can be explained by either the internal motivation of tourists or the external motivation originating from the destination.The purpose of this paper is to critically review the literature to build an appropriate research framework for understanding the formation of destination image by international tourists. Design, Methodology and Approach – The literature pertaining to destination image till recently can be divided into three evolutionary stages with stage boundaries marked by the seminal reviews by Echtner & Ritchie in 1991 and by Pike in 2002. The two main focuses of the destination image research are – measurement and theory of the destination image. The evolution of measurement and theory is reviewed, in this conceptual paper, through these stages justifying the proposed new research framework.Findings – The existing theories do not take in to account some of the modern variables such as perceived risks of travel and the power of social networks that fuel word of mouth. Originality of Research – All the conceptual discussions and views are original.